TRADISI BARANTAM DALAM PERKAWINAN DI JORONG KAYU JAO NAGARI BATANG BARUS KECAMATAN GUNUNG TALANG KABUPATEN SOLOK MENURUT PERSPEKTIF AL-‘URF - Nazra Hafizatul Hasana; Yusnita Eva (UIN Imam Bonjol Padang, 2020)
This research is motivated by the existence of the barantam tradition in a series of Walimatul al-Ursy events carried out by the people of Nagari Batang Barus. This tradition generally applies in Jorong Kayu Jao which has been passed down from generation to generation from previous ancestors to the present. Initially this tradition existed because of the help of the ninik mamak and the female relatives to the bride but over time this changed to competition and competition that was no longer healthy. The formulation of the problem in this study is how the background of the barantam tradition carried out by the Jorong Kayu Jao Nagari Batang Barus District of Gunung Talang District, Solok Regency and how the implementation of the barantam tradition carried out by the Jorong Kayu Jao Nagari Batang Barus community, Gunung Talang District, Solok Regency according to the perspective of Islamic law . The objectives to be achieved in this study are to explain the background of the tradition of barantam in marriage in Jorong Kayu Jao Nagari Batang Barus, Gunung Talang District, Solok Regency and to know the Islamic legal view of the marriage tradition that occurs in Jorong Kayu Jao Nagari Batang Barus, Gunung Talang District, Solok Regency. . This research is a field research (field research) using qualitative methods, which relies on data collection by observation and interviews. The tradition of barantam carried out by the people of Jorong Kayu Jao Nagari Batang Barus, Gunung Talang District, Solok Regency is a tradition that originates from their previous ancestors and is still preserved today. barantam is a ninik mamak, a relative, a woman who collects money at night after holding a Walimatul al-Ursy in the afternoon. For couples who do not practice the barantam tradition, the marriage is considered incomplete, flawed and is suspected of having the marriage due to forbidden acts committed by both parties, this can be a derivative punishment for the children and grandchildren because the parents' marriages are not cultic. According to the perspective of Islamic law, the tradition of barantam carried out by the community in Jorong Kayu Jao is not fully in accordance with Islamic law because there are still elements that are detrimental to the parties concerned. There is discrimination for those who do not commit and also a loss of sincerity for the parties involved in it. This includes